1) Упростите выражение:a) 2(с+1)^2-4c=b) 4a(a-2)-(a-4)^2=2) Разложите на множители:a) x^3-9x=b) 16x^4-81= 

1) Упростите выражение: a) 2(с+1)^2-4c= b) 4a(a-2)-(a-4)^2= 2) Разложите на множители: a) x^3-9x= b) 16x^4-81=  
Гость
Ответ(ы) на вопрос:
Гость
1) Упростите выражение: a) 2(с+1)^2-4c=2(c^2+2c+1)-4c=2c^2+4c+2-4c=2c^2+2 b) 4a(a-2)-(a-4)^2=4a^2-8a-a^2+8a-16=3a^2-16 2) Разложите на множители: a) x^3-9x=x(x-3)(x+3) b) 16x^4-81=(4x^2-9)(4x^+9)=(2x-3)(2x+3)(4x^+9)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы